2014
DOI: 10.3906/sag-1308-30
|View full text |Cite
|
Sign up to set email alerts
|

Possible metabolic impact of Ramadan fasting in healthy men

Abstract: Background/aim: Insulin sensitivity and β-cell function during Ramadan fasting in healthy male subjects have not been investigated so far. We assessed the changes of these and other metabolic parameters to judge the potential metabolic benefits of Ramadan fasting.Materials and methods: Twenty-four healthy males of Turkish origin living in Germany, with normal glucose tolerance, participated in this study during Ramadan of 2009; 19 who completed fasting were analyzed. Blood was drawn at sunset after a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The presence of the MetS has also been associated with lower plasma adiponectin levels (117) , indicating adipose tissue dysfunction and a two-to four-times increased risk for developing CVD and type 2 diabetes (118) . Similarly, several reports have indicated RDIF was associated with variable increments in adiponectin levels in fasting people (119)(120)(121) . Recently, we found that RDIF was associated with significant reduction in visceral fat surface area (measured by MRI) in fifty-seven overweight/obese participants, concomitant with significant reductions proinflammatory cytokines (IL-6 and TNF-α), and a significant increase in the anti-inflammatory cytokine IL-10 (122) .…”
Section: Discussionmentioning
confidence: 69%
“…The presence of the MetS has also been associated with lower plasma adiponectin levels (117) , indicating adipose tissue dysfunction and a two-to four-times increased risk for developing CVD and type 2 diabetes (118) . Similarly, several reports have indicated RDIF was associated with variable increments in adiponectin levels in fasting people (119)(120)(121) . Recently, we found that RDIF was associated with significant reduction in visceral fat surface area (measured by MRI) in fifty-seven overweight/obese participants, concomitant with significant reductions proinflammatory cytokines (IL-6 and TNF-α), and a significant increase in the anti-inflammatory cytokine IL-10 (122) .…”
Section: Discussionmentioning
confidence: 69%
“…Muslims markedly change their dietary patterns during the holy month of Ramadan, when they decide to fast from dawn to dusk. Several studies investigating the possible health and metabolic impact of this type of fasting have described beneficial effects on body weight, blood glucose concentration and lipid profiles . However, their results were highly variable because of differences in gender, age, dietary habits and ethnicity.…”
Section: Chronobiological Approaches To Tackle Obesitymentioning
confidence: 99%
“…It has been suggested that the synthesis of very low-density lipoprotein (VLDL), a triacylglycerol-rich particle, is increased in hepatocytes in response to reduced insulin action under fasting conditions [ 76 ]. It is suggested that Ramadan fasting results in a transient reduction in insulin sensitivity, which is compensated by an improved β-cell function with no significant change in glucose concentrations [ 37 ]. It has been reported that increased levels of glucagon and low levels of insulin augment lipolysis and ketogenesis [ 26 ].…”
Section: Resultsmentioning
confidence: 99%